Air Compressor Design and Construction With Esp32 Based Microcontroller Monitoring System - Junaedy Surya Tutuko; Agus Prawoto; Dyah Ratnaningsih; Antonius Edy Kristiyono; Shofa Dai Robbi (International Journal of Science and Environment (IJSE), 2026)
: Air compressors serve as vital auxiliary engines on ships for starting main engines and operating valves, yet manual monitoring leads to inefficiencies and frequent failures, contributing to 20% of machinery downtimes globally. This study aims to design and build a prototype air compressor with ESP32-based microcontroller monitoring system for real-time electrical parameter tracking. Employing an experimental prototype development design, the research utilized laboratory-scale prototype as subject, with hardware including PZEM-004T sensor, LCD I2C, and Blynk app; data analyzed via comparative quantitative measurements against standard multimeter for accuracy assessment. Results demonstrate 100% consistency in voltage (230V), current (6.1A), power (1015W), and frequency (50Hz) readings across LCD and remote app during static/dynamic tests. In conclusion, the prototype enhances predictive maintenance and educational training for maritime students, although field testing in harsh conditions is recommended